DIVERSIFIKASI PENGOLAHAN BUAH NENAS DESA GALANG DALAM MENINGKATKAN PENDAPATAN PETANI NENAS - Ekawati Ekawati; Sondang Sylvia Manurung; Ellyta Ellyta; Donna Youlla (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
Pineapple is one of the tropical fruit which consume by society because of the price is cheap, easily to get, high nutrition and easily cultivated. The partners of the dedication were Mitra Tani 1 Farmer’s Group and Galang Jaya Farmer’s Group. The objectives and special targets from the IbM was to establish and to develop the partner capability to process the pineapple become high valuable processed product namely: jam, lunkhead and nata de pina. Methods used in the program include: consultation, training and counseling assistance. Application of the methods to partner were: (1) Education of community through extension that aims to improve understanding partner about the economics benefit if they processed the product, (2) training the partners to process the pineapple become jam, lunckhead, and nata de pina, (3) facilitation and consultation in order to register the product, (4) Combination the diffusion of technology, education and training to improve competitiveness the product through packaging. The result of the program was the increase of knowledge from the partners about jam and lunkhead pineapple and the partners have a permission of household product (PIRT) from health Department of Pontianak Disctrict. Keywords : Pengolahan, Diversifikasi buah nenas, Nata de Pina